Downregulation of circNRIP1 Suppresses the Paclitaxel Resistance of Ovarian Cancer via Regulating the miR-211-5p/HOXC8 Axis - Li, Meng (Cancer Manag Res, 2020)
BACKGROUND: Circular RNA (circRNA) has an essential regulatory role in the chemotherapy resistance of cancers. Nevertheless, the role of circRNA nuclear receptor-interacting protein 1 (circNRIP1) in the paclitaxel (PTX) resistance of ovarian cancer (OC) remains unclear. MATERIAL AND METHODS: The circNRIP1, miR-211-5p and homeobox C8 (HOXC8) expression levels were assessed using qRT-PCR. The PTX resistance of cells was measured by 3-(4, 5-dimethylthiazolyl-2-yl)-2-5 diphenyl tetrazolium bromide (MTT) assay. Furthermore, cell proliferation, apoptosis, migration and invasion were detected by colony formation assay, flow cytometry and transwell assay, respectively. Moreover, the protein levels of proliferation, apoptosis, metastasis-related markers and HOXC8 were determined by Western blot (WB) analysis. Tumor xenograft models were constructed to explore the influence of circNRIP1 on OC tumor growth. The interaction between miR-211-5p and circNRIP1 or HOXC8 was confirmed by dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay. RESULTS: CircNRIP1 was highly expressed in PTX-resistant OC tissues and cells. Silencing of circNRIP1 repressed the PTX resistance of OC cells in vitro and OC tumor in vivo. Furthermore, circNRIP1 sponged miR-211-5p, and miR-211-5p inhibitor could reverse the inhibitory effect of circNRIP1 knockdown on the PTX resistance of OC cells. In addition, miR-211-5p targeted HOXC8, and HOXC8 overexpression could reverse the suppression effect of miR-211-5p on the PTX resistance of OC cells. Additionally, the expression of HOXC8 was regulated by circNRIP1 and miR-211-5p. CONCLUSION: CircNRIP1 silencing could inhibit the PTX resistance of OC via regulating the miR-211-5p/HOXC8 axis, showing that circNRIP1 might be a potential target for OC resistance treatment.